Pesantren: Problematika dan Solusi Pengembangannya - Dafri Harweli; Wedra Aprison (Departement of Mathematics Education, 2024)
This research is to find out the problems and solutions for development in Islamic boarding schools. This research uses a library research method with a qualitative approach. Problems and challenges of Salaf (traditional) Islamic boarding school education: 1) human resources. 2) source of funds, 3) limited facilities and infrastructure. 4) Problems with communication access to the outside world. 5) the Islamic boarding school tradition which still adheres closely to centric kiai. 6) very strong tradition of Salaf Islamic boarding schools places emphasis on the transmission of classical knowledge. 7) specialization at Salaf Islamic boarding schools in certain fields, for example Sufism oriented or Ushul fiqh oriented. 8) the Salaf Islamic boarding school curriculum is less relevant to current developments, and 9) institutional management. The challenges faced by Salaf Islamic boarding schools are competition with modern Islamic boarding schools and public schools, the stigma of being a place for radical Islamic cadres. Meanwhile, the problems and challenges of Khalaf (modern) Islamic boarding school education are the conflict between old ulama and young ulama and the existence of dichotomy or discreteness. Problems originating from students, curriculum, learning methods. facilities and infrastructure, influence of the western world and politics. The solution to Islamic boarding school problems is that educational programs must be repaired, updated and rebuilt, including reformulation of vision, objectives, curriculum, institutional management, educational methods and strategies, infrastructure, administration and so on.